The Great Cross-Border Bank Deleveraging: Supply Constraints and Intra-Group Frictions - Cerutti, Eugenio; Claessens, Stijn (Review of Finance, 2017)
Abstract International banks greatly reduced direct cross-border and local affiliates’ lending as the global financial crisis strained their balance sheets, lowered borrower demand, and altered government policies. Using bilateral lender–borrower data and controlling for demand, we show that reductions largely varied in line with markets’ prior assessments of banks’ vulnerabilities, with financial statements’ and lender–borrower data playing minor roles. Those banking systems subject to less market discipline, however, were less sensitive to markets’ perceptions. Moving resources within banking groups became more restricted as drivers of reductions in direct cross-border loans differed from those for local affiliates’ lending, especially for more impaired banking systems.